Long-term Effect of Colchicine Treatment in Preventing Urethral Stricture Recurrence After Internal Urethrotomy - sinanoglu, orhun; Kurtulus, Fatih Osman; Akgün, Feride Sinem (Urology Journal, 2018)
Purpose: Urethral stricture, known as a scar formation leading to urethral lumen stricture in sub-epithelial tissue, is the most common late complication of transurethral prostate resection (TURP). The aim of study is to evaluate efficacy of colchicine treatment in preventing urethral stricture recurrence in patients after internal urethrotomy, and to determine whether colchicine treatment had a sustained effect in decreasing stricture recurrences in patients with concomitant diseases. Methods: Patient data with weak urine stream and/or voiding difficulty, and who had internal urethrotomy in Urology Department of Maltepe University Hospital between dates 01 January 2011 and December 2016 were collected. They were randomized to colchicine receiving, and non-receiving arms. Colchicine was given 1 g/day orally for two months, and primary efficacy point was defined as urethral stricture development in 3, 6, and 12 months after internal urethrotomy. Results: The study was conducted on 84 males with the mean age of 67.7 ± 7.5 years. The mean ages of colchicine receivers and non-receivers were 68.2 ± 7.6 and 67.1 ± 7.6 years, respectively. Recurrence rate of urethral stricture was significantly lower in colchicine receivers (P = .044) than non-receivers. In overall evaluation, recurrence rate of urethral stricture was significantly low, if there was only one comorbidity (P = .006), but rates were significantly higher in presence of three (P = .010) and four (P = .040) comorbidities. No significant difference in recurrence rates was determined in patients without comorbidities or with two comorbidities (P > .05). Conclusion: Combination of oral colchicine with internal urethrotomy reduces recurrence rates of urethral stricture significantly.